Hijrah Intention and Customer Decisions to Use Islamic Banks: Development of Theory of Planned Behavior - Al Umar, Ahmad Ulil Albab; Setyono, Joko (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2023)
This study aims to analyze the determinants of hijrah intention and customers' decisions to use Islamic banks. This study carries out the development of a theory of planned behavior which consists of attitude factors, subjective norms and behavior control. The development that is done is to modify the intention in the theory of planned behavior to become hijrah intention. Another development is adding the factor of Islamic branding to analyze its effect on hijrah intention and customer decisions. The next development is to link the influence of hijrah intention on customer decisions. Other developments also add a moderating construct, namely Islamic financial literacy with the aim of Islamic financial literacy can be a determinant of strengthening or weakening the variable of hijrah intention towards customer decisions. This study is a study with a quantitative approach. The population in this study are all customers of Islamic banks in Indonesia. The sample of this research is 275 respondents from 34 provinces in Indonesia. Data analysis used SEM with the SmartPLS 3 application. The results in this study indicate that the theory of planned behavior which consists of attitude variables, subjective norms and behavioral control and Islamic branding variables has a significant positive effect on hijrah intention. Islamic branding also has a significant influence on customer decisions. Hijrah intention has no significant effect on customer decisions. Islamic financial literacy weakens the effect of hijrah intention on customer decisions.